The Legal Consequences of China’s Objection Against Permanent Court of Arbitration’s Awards on International Law - Winardi; Chomariyah (Fakultas Hukum Universitas Hang Tuah, 2018)
South China Sea (SCS) dispute has been running for so long. The claimant states keeps endeavoring various resolutions to settle that dispute, either through reconcilement by their own choice or under several compulsory procedures provided by UNCLOS 1982 (Convention). Considering the content of UNCLOS 1982, one of the claimant states, Philippines, brought the dispute to PCA unilaterally against China which objected the jurisdiction along with its final award through official government statements and verbal notes. China was found violating International Law based on the principle of Pacta Sunt Servanda. Nine Dash Lines claimed based on Historic Rights are still retained by China. The procedures should lead to a permanent resolution by International Community to avoid any possible armed conflicts, including the likelihood that Historic Rights turned into Customary International Law.